Posterior argentinean flag-like sign during primary posterior continuous curvilinear capsulorhexis - Marques,Frederico França (2017)
ABSTRACT We describe a unique complication during primary posterior continuous curvilinear capsulorhexis (PCCC) in a patient with megalocornea scheduled for phacoemulsification with toric multifocal intraocular lens (IOL) implantation. After nucleus emulsification and cortex removal, the capsular bag was filled with cohesive viscoelastic in preparation for PCCC to achieve reverse optic capture of the IOL, thus ensuring stability. However, as soon as the initial puncture was made using a 27-gauge needle to start the capsulotomy, the posterior capsule opening extended peripherally from 0º-180º. This capsule extension was similar to the Argentinean-flag sign in hypermature cataracts, and both are caused by excessive intracapsular pressure. Careful bimanual manipulation was performed to implant the IOL on the desired axis, which occurred uneventfully. At a postoperative visit, the patient exhibited excellent uncorrected visual acuity with a well-aligned IOL.